Using Natural Antioxidants with or Without Sulphate to Improve Productive and Reproductive Performance of Two Local Strains at Late Egg Production Period - Ali , M.N.; Hassan, M.S.; El-Ghany, F.A. Abd; Awadein, Nasra B. (International Journal of Poultry Science, 2012)
This study examines the hypothesis that natural antioxidants can improve the performance of local laying hens in late egg production period (48-60 weeks) especially in presence of sulphate ion. A total number of 288 hens plus 36 cocks 48 weeks old from Inshas and Dokki 4 strains (144 hens and 18 cocks from each strain) were equally divided into 12 groups with 3 replicates (8 hens + 1 cocks each) and housed in wire cages. The experimental hens fed from 48 to 60 week of age the control diet without or with 0.25% Cuminum cyminum L (CC), 0.5% Anhydrous Sodium Sulphate (SS), SS + CC, 20 mg commercial Canthaxanthin/kg diet (CAN) and CAN + SS. Compared to control diet, addition of CC, SS, CC + SS, CAN or CAN + SS increased egg number and egg yolk color score. All feed additives used in this study increased calcium, phosphorus, total protein, albumin, globulin and total antioxidants capacity in plasma while decreased LDL, HDL, total cholesterol and total lipids in both plasma and egg yolk. Feed additives increased T3 and estrogen hormones compared to control diet. Feed additives tended to improve semen quality parameters, fertility and hatchability of total and fertile eggs. The combination of CAN and SS was the most successful additive under the condition of this study. Further studies are needed to elucidate the mechanism of protecting hen hormones from free radical attack at the late egg production period.